SUSTAINABLE DEVELOPING FISHERIES IN THE INTEGRATED MANAGEMENT FRAMEWORK ON THE WEST COASTAL ZONE OF THE TONKIN GULF - Thung, Do Cong (Vietnam Journal of Marine Science and Technology, 2009)
Located on the North-West of East sea, the Tonkin Gulf is enclosed  by Vietnamese and Chinese coasts with the surface  124.500 km 2  and 1950 km sorrowing area. In the Vietnamese part, in the Tonkin Gulf contains over 3000 islands as Halong Bay, Catba islands, Bai Tu Long Bay etc. The Tonkin Gulf is very important area, there are many economical activities are going as caching, marine transport, mine exploitations and marine tourism. By this important, very long time ago, the fisheries study  in  the  Tonkin  Gulf  was  proceed.  The  results  show  that  in  the  Tonkin  Gulf  are  very  high biodiversity,  richness  ecosystems  giving  potent  ion  for  marine  ecotourism.  But,  the  fishery  stock concentrates  on  the  coastal  zone  and  very  sensible  and  declining.  By  this  reasons,  the  strategy  of sustainable fisheries exploitation is exploiting parallel with the protection. The works are resolved only by connecting closely between plan exploitation with the coastal zone integrated management. The main objects are sustainable exploitation, sustainable marinecuture and marine economy